Chinese Associations and the Making of Chinese Identities in Singapore (1819-1959) - Goda, Miho (Kasarinlan: Philippine Journal of Third World Studies; Vol 13 No 3 (1998): Social Forces and Communities in Southeast Asia, 2007)
The identity of the Chinese in Singapore took more than a century and half to develop. During British rule it began with one's place of origin and dialect or bang. The Chinese identity remained ethnically fragmented until the mainland became a republic. The emergence of communism was the next turning point as dissatisfied Chinese began identifying themselves as Singaporeans. These stages in the evolution and development of Chinese identities took place under the guidance of Chinese associations and the schools they established and managed in the Crown colony.